Can Public Works Programs Help the Poor During Crises? - World Bank (Washington, DC, 2014)
Economic crises can be particularly arduous for poor and vulnerable people. In particular, job losses stemming from economic downturns undercut the ability of more vulnerable households to support themselves. Public works programs, which help sustain poor households through temporary employment, are one method used by governments to lessen the impacts of crises. The World Bank is focused on helping countries end poverty. Key to this knows which programs do and do not yield tangible results. To help policymakers assess the effectiveness of Latvia's public works program, the World Bank supported an evaluation of the government-sponsored public works initiative, which was launched in response to the global financial crisis of 2008-2010. The evaluation found that the program successfully reached its intended target, helping Latvia's worst-off cope with the crisis by increasing their short-term incomes. For policymakers and development experts, this evaluation underscores the usefulness of public works programs as emergency social safety net instruments even in upper-middle income countries.